A Review of Biological and Sustainable Management Approaches for Alphitobius diaperinus, a Major Pest in Poultry Facilities - Ozge Tufan-Cetin; Huseyin Cetin (Veterinary Sciences)
The lesser mealworm (Alphitobius diaperinus) is a significant pest in poultry facilities, transmitting pathogens such as Salmonella and causing structural damage in poultry operations. Challenges such as insecticide resistance and environmental concerns associated with the widespread use of traditional insecticides underscore the need for sustainable alternatives. This review examines biological and sustainable management strategies for managing the lesser mealworm, including entomopathogenic fungi, bacteria, nematodes, plant essential oils-extracts, pheromones, and diatomaceous earth. These eco-friendly approaches highlight fungi and nematodes for their effectiveness in larval control and essential oils for their insecticidal and repellent properties. The application of pheromones and diatomaceous earth further complements other methods within integrated pest management (IPM) systems. Integrating these biological tools into IPM offers a sustainable and effective solution for reducing A. diaperinus populations, addressing both health and environmental concerns.